2019
DOI: 10.1029/2019ea000855
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Satellite‐Based Precipitation at Sub‐Daily Time Scales Over a High‐Profile Watershed with Complex Terrain

Abstract: In this study, a preliminary quantitative evaluation of global precipitation measurement (GPM) mission precipitation products at sub-daily time scales was performed in a typical and small watershed with complex terrain in southwestern China. The world heritage Jiuzhaigou Valley, which has been affected by many rainfall-triggered debris-flow disasters after the Ms 7.0 earthquake on 8 August 2017, was selected as the study area. The "early", "late" and "final" half-hourly GPM precipitations and hourly observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…We use the gridded rainfall dataset to check the reliability of the new GPM data for future application in debris-flow monitoring and warning. Correlation coefficients of 0.67, 0.53, and 0.56 are obtained for Jiuzhaigou, Wenchuan, and Lushan areas, respectively, (Figure 6), which indicates that the reliability needs to be further improved, as also confirmed by Liu et al (2019). Though any satellite-based method will cause inevitable uncertainties (Carr et al, 2015), a combination with the methods used in this study could be an important supplement for debrisflow warning in ungauged areas with earthquakes.…”
Section: Implication For Post-quake Debris-flow Warningmentioning
confidence: 65%
“…We use the gridded rainfall dataset to check the reliability of the new GPM data for future application in debris-flow monitoring and warning. Correlation coefficients of 0.67, 0.53, and 0.56 are obtained for Jiuzhaigou, Wenchuan, and Lushan areas, respectively, (Figure 6), which indicates that the reliability needs to be further improved, as also confirmed by Liu et al (2019). Though any satellite-based method will cause inevitable uncertainties (Carr et al, 2015), a combination with the methods used in this study could be an important supplement for debrisflow warning in ungauged areas with earthquakes.…”
Section: Implication For Post-quake Debris-flow Warningmentioning
confidence: 65%
“…Liu et al . (2019) indicated that the changes in total precipitation for the subregions of China were closely related to the occurrence and development of precipitation vertical structures. Figure 6 presents integrated nonliquid water path (IWP in mm), integrated liquid water path (LWP in mm), total water path (TWP in mm, TWP = IWP + LWP) and ratio of liquid water path (RLWP, that is, LWP/TWP) for AHREs caused by stratiform and convective rainfalls over different terrains.…”
Section: Resultsmentioning
confidence: 99%
“…The region of southwest China, located in the east of the Tibetan Plateau (TP) and characterized by complex topography, is prone to frequent AHREs in warm season (Zheng et al ., 2016; Liu et al ., 2019). Many studies focus on climatological aspects of AHREs, such as occurrence frequency, intensity, diurnal variations, synoptic conditions and meso‐α‐scale environmental conditions (Wang and Zhou, 2005; Xiao and Chen, 2010; Zhang et al ., 2019; Gao and Li, 2020; Li et al ., 2020; Chen et al ., 2020a; 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Effectiveness and accuracy of precipitation measurement play a critical role in disaster mitigation in the area. Furthermore, most gridded precipitation datasets from climate model outputs, and reanalysis products, are not ideally suited for investigating precipitation‐triggered geological hazards in this region because they tend to overestimate the amount of heavy precipitation over the TP and complex topography (Liu et al ., 2019; Gu et al ., 2020). Detailed investigation of the precipitation characteristics around the YGC could provide the fundamental information required for understanding the region's atmospheric processes, which in turn are critical to understanding its cryospheric and hydrological processes.…”
Section: Introductionmentioning
confidence: 99%